A novel, dynamic pattern-based analysis of NF-κB binding during the priming phase of liver regeneration reveals switch-like functional regulation of target genes - Cook, Daniel J.; Patra, Biswanath; Kuttippurathu, Lakshmi; Hoek, Jan B.; Vadigepalli, Rajanikanth (Frontiers in Physiology, 2015)
Following partial hepatectomy, a coordinated series of molecular events occurs to regulate hepatocyte entry into the cell cycle to recover lost mass. In rats during the first 6 h following resection, hepatocytes are primed by a tightly controlled cytokine response to prepare hepatocytes to begin replication. Although it appears to be a critical element driving regeneration, the cytokine response to resection has not yet been fully characterized. Specifically, the role of one of the key response elements to cytokine signaling (NF-κB) remains incompletely characterized. In this study, we present a novel, genome-wide, pattern-based analysis characterizing NF-κB binding during the priming phase of liver regeneration. We interrogated the dynamic regulation of priming by NF-κB through categorizing NF-κB binding in different temporal profiles: immediate sustained response, early transient response, and delayed response to partial hepatectomy. We then identified functional regulation of NF-κB binding by relating the temporal response profile to differential gene expression. We found that NF-κB bound genes govern negative regulation of cell growth and inflammatory response immediately following hepatectomy. NF-κB also transiently regulates genes responsible for lipid biosynthesis and transport as well as induction of apoptosis following hepatectomy. By the end of the priming phase, NF-κB regulation of genes involved in inflammatory response, negative regulation of cell death, and extracellular structure organization became prominent. These results suggest that NF-κB regulates target genes through binding and unbinding in immediate, transient, and delayed patterns. Such dynamic switch-like patterns of NF-κB binding may govern different functional transitions that drive the onset of regeneration.